GelFAP: Gene Functional Analysis Platform for Gastrodia elata - Yang, Jiaotong; Xiao, Qiaoqiao; Xu, Jiao; Da, Lingling; Guo, Lanping; Huang, Luqi; Liu, Yue; Xu, Wenying; Su, Zhen; Yang, Shiping; Pan, Qi; Jiang, Weike; et al. (Frontiers in Plant Science, 2020)
Gastrodia elata, also named Tianma, is a valuable traditional Chinese herbal medicine. It has numerous important pharmacological roles such as sedation, anticonvulsant, anti-aging and lowering blood pressure, and also has effects on immune and cardiovascular system. The whole genome sequencing of G. elata has been completed in recent years, which provides strong support for the construction of G. elata gene functional analysis platform. Therefore, in our research, we collected and processed 39 transcriptome data of G. elata and constructed the G. elata gene co-expression networks, then we identified functional modules by WGCNA package. Furthermore, gene families of G. elata were identified by tools including HMMER, iTAK, PfamScan and InParanoid. Finally, we constructed a gene functional analysis platform for G. elata (http://www.gzybioinformatics.cn/Gel). In our platform, we introduced functional analysis tools such as BLAST, GSEA and cis-elements (motif) enrichment analysis tool. In addition, we identified 19 genes which might participate in biosynthesis of gastrodin and predicted 19 mannose-binding lectin antifungal proteins of G.elata, we also introduced the usage of GelFAP by analysis CYP51G1 and GFAP4 gene. Our platform GelFAP may help researchers to explore the gene function of G. elata and make novel discoveries about key genes involved in biological processes of gastrodin.